Talar fractures: long-term results - Pogliacomi, F.; De Filippo, M.; Soncini, G.; Frattini, M. (Acta Biomedica Atenei Parmensis, 2009)
Background: talar fractures are rare and potentially invalidating injuries. Traditional x-ray projections often do not provide comprehensive and exhaustive view of the talus; in order to determine the best therapeutic strategy and obtain early and precise prognostic data diagnostic examination usually includes oblique projections and computed tomography scans. In displaced fractures treatment is surgical, with percutaneous or open osteosynthesis. Methods: 16 patients affected by talar fractures were treated and assessed with the Ankle Hindfoot Scale, the Ankle Osteoarthritis Scale and radiographic investigation. Results: consolidation was obtained in all cases. None avascular bone necrosis was observed at the follow-up. Mean score divided into the two components was 69.3 on the first scale and 38.4% on the second scale. Conclusions: talar fractures are challenging injuries for orthopedic surgeon. The evolution of this type of fractures, above all in the most complex fractures of the body and of the neck, is often poor and characterized by severe complications. Early treatment is important for recovery.